Approval Summary: Azacitidine for Treatment of Myelodysplastic Syndrome Subtypes - Kaminskas, Edvardas; Farrell, Ann; Abraham, Sophia; Baird, Amy; Hsieh, Li-Shan; Lee, Shwu-Luan; Leighton, John K.; Patel, Hasmukh; Rahman, Atiqur; Sridhara, Rajeshwara; Wang, Yong-Cheng; Pazdur, Richard (Clinical cancer research, 2005)
Purpose: This article summarizes data submitted to the U.S. Food and Drug Administration for marketing approval of azacitidine as injectable suspension (Vidaza, Pharmion Corporation, Boulder, CO) for treatment of patients with myelodysplastic syndrome. Experimental Design: In one phase 3 controlled trial, 191 study subjects were randomized to treatment with azacitidine or to observation; an additional 120 patients were treated with azacitidine in two phase 2 single arm studies. The primary efficacy end point was the overall response rate, defined as complete or partial normalization of peripheral blood counts and bone marrow blast percentages for at least 4 weeks. Results: In the controlled trial, the overall response rate was 15.7% in the azacitidine treatment group; there were no responders in the observation group ( P < 0.0001). Response rates were similar in the two single arm studies. During response patients stopped being red cell or platelet transfusion dependent. Median duration of responses was at least 9 months. An additional 19% of azacitidine-treated patients had less than partial responses, most becoming transfusion independent. The most common adverse events attributed to azacitidine were gastrointestinal, hematologic, local (injection site), and constitutional. There were no azacitidine-related deaths. Conclusions: On May 19, 2004 the U.S. Food and Drug Administration approved azacitidine as injectable suspension for treatment of patients with the following myelodysplastic syndrome subtypes: refractory anemia or refractory anemia with ringed sideroblasts (if accompanied by neutropenia or thrombocytopenia or requiring transfusions), refractory anemia with excess blasts, refractory anemia with excess blasts in transformation, and chronic myelomonocytic leukemia. Full prescribing information is available at http://www.fda.gov/cder/foi/label/2004/050794lbl.pdf . Azacitidine is the first agent approved for treatment of myelodysplastic syndrome.